Litterfall production and composition analysis of mangrove forests along Ormoc Bay, Ormoc City, Philippines - Cala, Ramnele S.
The litterfall production and composition of mangrove forests along Ormoc Bay, Ormoc City from May 2022 to February 2023 was assessed in this study. Using 1 m2 litter traps, litterfall was collected for 10 months in selected natural, reforested, and colonized mangrove stands. The mean total litterfall of all the sampled mangrove stands was 9.07 +/- 0.85 Mg DW ha---1 yr -1, which is within the range of the mangrove litterfall production of tropical mangrove forests. Colonized mangrove stands yielded the highest litterfall production (14.70 +/- 3.68 Mg DW ha---1 yr -1). Leaf litterfall contributed the most to the litterfall productivity of Ormoc Bay mangrove forests, which reached a proportion of 84% in May. The variability of litterfall production was higher during the wet season, but seasonal variability was only statistically significant for reproductive litterfall. Additionally, only a few significant correlations were discovered for total litterfall and its parts with forest characteristics and climatic conditions, suggesting a greater influence of other factors to litterfall productivity. The findings of this study strengthen the evidence for the effectiveness of mangrove conservation, given the comparable litter production of colonized and reforested stands to natural mangrove ecosystems.